Simple Interactive Contents Based English Materials Development for Non-English Departments - Wahyu Kamil Syarifaturrahman; Dedi Aprianto; Zainuddin Abdussamad; Sutarman Sutarman (Humanitatis : Journal of Language and Literature, 2022)
The efforts of curriculum development led by the learners’ needs and necessities. English curriculum design in the tertiary education must be dynamic by following the learning patterns and learning styles of students as active participants in ELT. Another perspective in improving English Language Learning through an English textbook design by developing simple-interactive contents in purpose of better English learning outcomes. This study aims at developing a model of English textbook based on the interactive-simple and meaningful contents and investigating whether the use of such English textbook can increase ELT effectiveness. It was conducted under the perspective and methods of Research and Development (R&D) through; explorative study, curriculum model development study and evaluative study. The data was collected through observation, questionnaires, and test. Eventually the data was statistically analyzed through t-test. This study revealed that the needs-analysis’ findings on necessity, wants; the four language skills and components such as interactive Grammar contents, Writing skills; The Organizations of the Paragraph, Reading Skills, Pronunciation (Sound-Structures, and related English. Simple-interactive contents-based English textbook was appropriately-enough used. Moreover the finding was supported by test through T-test showing that the effect is not too significant between the participants using the developed textbook (81.10) with those are not using one (77.26). This developed textbook is rather appropriate to use in the non-English departments in tertiary education. It can further be developed by designing the appropriate contents and assessment models. One significant fact found in this study is that the designed materials would have made non-English students engage in positive classroom activities; English exposure and active participation.